Charles Fenton Mercer correspondence - Mercer, Charles Fenton, 1778-1858.
Letter (1825) and correspondence (1832) regarding loans for the Chesapeake and Ohio Canal. Includes an ALS (1832 December 25) from John Peter Van Ness to Phineas Janney pertaining to the loans.
U.S. representative from Virginia, U.S. army officer, and canal official.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Portion of the collection formerly cataloged under Washington (D.C.) Letters, 1832.
Keywords: Janney, Phineas -- Correspondence; Van Ness, John Peter, -- 1770-1846 -- Correspondence; Chesapeake and Ohio Canal (Md. and Washington, D.C.); Canals -- Maryland; Canals -- Washington (D.C.); Army officers; Canal officials; Representatives, U.S. Congress -- Virginia